2013
DOI: 10.1002/crat.201300123
|View full text |Cite
|
Sign up to set email alerts
|

Transient analysis of the cooling process and influence of bottom insulation on the stress in the multicrystalline silicon ingot

Abstract: Directional solidification is one of the most popular techniques for massive production of multicrystalline silicon. After growth and annealing, the ingot is cooled down by a designed cooling process, which is initialized by descending bottom insulation, and then is controlled both by power ramp-down rate and by motion of the bottom insulation. Thermal stress is piled up during cooling, and associated crystal defects, such as dislocation and micro-cracks, may generate and propagate in the ingot. In the paper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Nakano et al [3] investigated the effects of the cooling rate on dislocation density, and they found that the maximum dislocation density was decreased and that of residual stress was increased during a fast cooling process. Wang et al [4] found that the dislocation-free regions and thermal stress were significantly affected by the bottom insulation motion, and deemed the sinusoidal motion of the bottom insulation is probably better for the improvement of the ingot quality. Zhou et al [5,6] proposed a modified cooling process with lower temperatures of both thermocouples 1 and 2, and they found that the final dislocation density could be reduced significantly with the modified cooling process.…”
Section: Introductionmentioning
confidence: 99%
“…Nakano et al [3] investigated the effects of the cooling rate on dislocation density, and they found that the maximum dislocation density was decreased and that of residual stress was increased during a fast cooling process. Wang et al [4] found that the dislocation-free regions and thermal stress were significantly affected by the bottom insulation motion, and deemed the sinusoidal motion of the bottom insulation is probably better for the improvement of the ingot quality. Zhou et al [5,6] proposed a modified cooling process with lower temperatures of both thermocouples 1 and 2, and they found that the final dislocation density could be reduced significantly with the modified cooling process.…”
Section: Introductionmentioning
confidence: 99%